2007
DOI: 10.1073/pnas.0701252104
|View full text |Cite
|
Sign up to set email alerts
|

Loss of blood–brain barrier integrity in the spinal cord is common to experimental allergic encephalomyelitis in knockout mouse models

Abstract: Experimental allergic encephalomyelitis (EAE) is an inflammatory demyelinating disease of the CNS that is used to model certain parameters of multiple sclerosis. To establish the relative contributions of T cell reactivity, the loss of blood-brain barrier (BBB) integrity, CNS inflammation, and lesion formation toward the pathogenesis of EAE, we assessed the incidence of EAE and these parameters in mice lacking NF-B, TNF-␣, IFN-␣␤ receptors, IFN-␥ receptors, and inducible nitric oxide synthase. Although increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 44 publications
1
55
3
Order By: Relevance
“…In recent studies the extent of BSCB disruption was shown to correlate with the severity of EAE, as measured by fluorometric analyses of whole homogenized spinal cords (55,73). In the present study, we did not find a direct correlation between the level of BSCB permeability and clinical score, but rather with the day of disease onset.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…In recent studies the extent of BSCB disruption was shown to correlate with the severity of EAE, as measured by fluorometric analyses of whole homogenized spinal cords (55,73). In the present study, we did not find a direct correlation between the level of BSCB permeability and clinical score, but rather with the day of disease onset.…”
Section: Discussioncontrasting
confidence: 49%
“…Hence, in our hands the EAE score is only partially related to the extent of BSCB disruption in the lumbar spinal cord and as such is not the optimal point of reference for reporting BSCB permeability. This slightly differs from other studies reporting a correlation between clinical severity and the extent of BSCB disruption, although they used different assays, immunization protocols, or mouse strains (4,55).…”
Section: Bscb Disruption Is Transient and Initiated Shortly Before Eacontrasting
confidence: 50%
“…A pivotal step in triggering of CNS inflammation is disruption of the blood-brain barrier (BBB) (25). We, therefore, next administered the EP4 agonist to mice from days 7 to 14, injected sodium fluorescein intraperitoneally on day 14, and then, quantified fluorescein incorporation into the spinal cord 30 min later.…”
Section: Resultsmentioning
confidence: 99%
“…Both knockout strains bear an H-2b haplotype, which confers susceptibility to MOG -induced EAE. However, Prl 2/2 mice were backcrossed into C57BL/6 background, which is known to be more susceptible to EAE development than the 129 background, into which Prlr 2/2 mice were backcrossed (26,27). All procedures involving animals were approved by the Institute Ethical Committee and performed in accordance to institutional guidelines and national law (DL116/92), and carried out according to the Principles of Laboratory Animal Care (European Communities Council Directive 86/609/EEC).…”
Section: Micementioning
confidence: 99%